Formation of fluvial xenolandscapes of Martian valleys and channels - Serhii, Kyryliuk (Dnepropetrovsk University, 2024)
Contemporary concepts of Martian Valley formation and the current state of their study are examined. Three-dimensional modeling was conducted using the examples of two regions on Mars, the Lani Chaos Region and Kasei Vallis, to determine and map the main morphological features typical of Martian valleys as a basis for identifying xenolandscapes. The xenaxiomatic author’s concept was applied as a means of investigating xenolandscape diversity on the surface of Earth-like planets, in this case, Mars. The xenaxiomatic concept is the result of incorporating and utilizing traditional knowledge of the differentiation and application of axioms of cognition. Specialized for xenoplanetological use, this integrative cognitive tool is a variant of an axiomatic approach. The main essence of this approach, in the case of distinguishing xenolandscapes, lies in developing a unified scheme for searching for corresponding xenolandscape elements that are axiomatically elementary fragments of the planet’s surface, followed by their classification and xenolandscape interpretation. Scientific awareness has been achieved by filling it with all available information from various natural sciences related to xenoplanetology and subsequent exploratory xenolandscape interpretation and synthetic cartographic representation of characteristic, typical local xenolandscape formations on Mars (part of the Kasei Vallis valley). These depicted objects are extra-rank, meaning they have not yet been ranked in terms of xenolandscape formations but are uniformly formed due to the synergy of influences and interactions of different forces, yet genetically stemming from the same xenolandscape-forming factors of material and energy-field xenonature. A mechanism for the formation of modern Martian valleys is proposed through the influx of heat flow and impact events. Exploratory xenolandscape studies, with their positions verified by this conducted research in terms of theoretical, methodological, and methodical content, have become an unexpected benchmark for the effectiveness of similar theoretical and methodological components of classical landscape science, with which the research capabilities of landscape science can and should be compared.
Keywords: Mars; valleys; channels; xenolandscapes; Lani Chaos Region; Kasei Vallis